Minat Beli Konsumen Teh Botol Kemasan terhadap Variasi Produk dan Kemasan Produk - Libriana Susanti (Journal of Management and Bussines (JOMB), 2021)
This study aimed to determine the effect of product variation, product packaging, and the effect of both (product variation, and product packaging) on ​​consumer buying interest in Sosro bottled tea at Lesehan Pak Gendut. This research used an Associative Quantitative research design. The data analysis technique used is the SPSS version 23.0 application, using data testing, and statistical testing. The results showed that product variation, product packaging, and their influence (product variation, and product packaging) respectively had Mean>Std values. Dev. (41,840>4,45091; 41,380>4,96062; 41,300>4,85399). The conclusion is that product variations and product packaging indicate an influence on consumer buying interest in bottled tea sosro at Lesehan Pak Gendut simultaneously and partially. Keywords: Product Packaging, Consumer Buying Interest, Product Variation